2006
DOI: 10.1007/s11664-006-0211-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrode material on transport and chemical sensing characteristics of metal/carbon nanotube contacts

Abstract: In this paper, we report on the electrical transport characteristics and sensitivity to chemical exposure of single wall carbon nanotube devices fabricated on Pd, plasma-oxidized Pd, and Au electrodes. When the devices are exposed to vapors from ammonia, ethanol, and water, the response of current to each chemical is unique. However, there is essentially no difference in response between devices with different electrode materials. This finding suggests that for the chemical species tested in this study, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…reported device response to NH 3 with SiO‐passivated NTFET device contacts, and using their experimental data they calculated that NH 3 adsorption resulted in a donation of 0.04 electrons per molecule,48 which is in perfect agreement with the value that Lee and co‐workers calculated 25. Similarly, Jones et al 49. concluded that NTFET device response to NH 3 exposure resulted from charge transfer with the CNT.…”
Section: Carbon Nanotube Based Environmental Sensorsmentioning
confidence: 56%
“…reported device response to NH 3 with SiO‐passivated NTFET device contacts, and using their experimental data they calculated that NH 3 adsorption resulted in a donation of 0.04 electrons per molecule,48 which is in perfect agreement with the value that Lee and co‐workers calculated 25. Similarly, Jones et al 49. concluded that NTFET device response to NH 3 exposure resulted from charge transfer with the CNT.…”
Section: Carbon Nanotube Based Environmental Sensorsmentioning
confidence: 56%
“…Dies stimmt genau mit dem bereits von Lee und Mitarbeitern berechneten Wert überein 25. Jones et al 49. schlussfolgerten ebenfalls, dass die Reaktion des NTFET bei NH 3 ‐Exposition aus einem Ladungstransfer mit der CNT resultiert.…”
Section: Unweltsensorenunclassified
“…Comparing with other CNT-based ethanol sensors, the best sensor response to 500 ppm ethanol at room temperature is 1.12 [9] and 1.07 [13], respectively. When the sensing temperature raises up to 165 • C, the sensor response increases to 1.38 [8].…”
Section: Ethanol-sensing Propertiesmentioning
confidence: 92%
“…Many important applications have been demonstrated, and both CNT-based [5][6][7][8][9][10][11][12][13] and CNT-doped [14][15][16][17][18][19][20] gas sensors were received considerable attention because of their nanometer hollow geometry, high specific surface area, high electron mobility, surface modification, and functionalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation